Mid-Term Follow-Up of Patient Reported Outcomes and Reoperation Rates for Minimal-Resection Total Ankle Arthroplasty. Issue 4 (November 2022) - Cohen, Billy; Ward, Patrick; Carney, Dwayne D.; Elliott, Ian; Fisher, Brian; McCormick, Jeremy J.; Backus, Jonathon D.
Category: Ankle Arthritis; Ankle Introduction/Purpose: The utilization of total ankle arthroplasty (TAA) is increasing in treatment of end-stage ankle arthritis. Modern implants show improved survival at 10-year and greater follow-up with patient reported outcomes exceeding those obtained with arthrodesis.1-5 Other benefits include maintaining ankle range of motion and decreased rate of adjacent joint arthrosis. The Infinity (Stryker, Mahwah, NJ), Salto-Talaris (Salto) (Smith & Nephew, Memphis, TN), and Scandanavian Total Ankle Replacement (STAR) (DJO Global, Lewisville, TX) TAA have become highly utilized implants due to minimal bone resection to preserve both tibial and talar bone stock. The purpose of this study is to determine implant survival, reoperation rate, and patient reported outcomes of minimal-resection total ankle implants. Methods: After obtaining IRB approval, a retrospective review was performed of all patients who underwent TAA between January 1, 2007 - December 31, 2018. Inclusion criteria, including minimum 2 year follow-up, and exclusion criteria left ninety- eight (98) patients for review. Primary outcome measures included patient-reported outcome measure information systems (PROMIS) scores preoperatively, 1-year and last follow-up. Secondary outcomes measures included reoperation and need for revision surgery as well as radiographic analysis at 3-months, 1-year, 2-year, 5-years and last follow up to identify loosening and lucency. Demographics including age, gender, race, body mass index (BMI), smoking status and diabetes were tabulated. Student's T-test compared PROMIS outcomes between the Infinity and Other groups. Chi-squared test investigated differences in categorical variables and a repeated-measure analysis of variance (ANOVA) was used to investigate differences between PROMIS scores for the Infinity group. Results: 75 Infinity and 23 STAR or Salto patients were identified, average follow up of 3.4 years (range of 5-months to 10.75- years). PROMIS scores for depression and anxiety were significantly lower at most recent follow-up for the Infinity group (p<0.05). Physical function and pain interference scores were not significantly different between groups (p>0.05). Infinity patients saw favorable improvements in anxiety, depression, physical function and pain interference scores postoperatively (p<0.05). A higher incidence of revision with Salto and STAR was observed when compared to Infinity (1 Infinity, 1 Salto, 4 STAR) (p<0.05). Salto and STAR groups presented more 5-year cysts than the Infinity group (p<0.05). Evidence of loosening was higher in the Infinity group at 5-years compared to Salto and STAR (1 Infinity, 0 Other, p<0.05). Finally, more lucency zones were identified at 3 months in Infinity group compared to Salto and STAR (p<0.05). Conclusion: TAA is a durable treatment for ankle osteoarthritis demonstrating equivalent physical function and pain inference PROMIS scores across all minimal resection implants. Patients who received Infinity had significant improvements in depression and anxiety PROMIS scores when compared to other implants at an average 3.4 year follow-up suggesting significant improvement in quality of life as measured by PROMIS between the preoperative and early/late term follow-up periods. Patients who underwent TAA with Infinity experienced lower rates of revision and a trend toward lower need for reoperation when compared to other minimal resection implants.